Investigating peripheral blood monocyte and T-cell subsets as non-invasive biomarkers for asymptomatic hepatic steatosis: results from the Multi-Ethnic Study of Atherosclerosis - Niedecker, Rhys W.; Delaney, Joseph A.; Doyle, Margaret F.; Sparks, Andrew D.; Sitlani, Colleen M.; Buzkova, Petra; Zeb, Irfan; Tracy, Russell P.; Psaty, Bruce M.; Budoff, Matthew J.; Olson, Nels C. (Frontiers in Immunology, 2024)
Background: Circulating immune cells have gained interest as biomarkers of hepatic steatosis. Data on the relationships between immune cell subsets and early-stage steatosis in population-based cohorts are limited. Methods: This study included 1944 asymptomatic participants of the Multi-Ethnic Study of Atherosclerosis (MESA) with immune cell phenotyping and computed tomography measures of liver fat. Participants with heavy alcohol use were excluded. A liver-to-spleen ratio Hounsfield units (HU) <1.0 and liver attenuation <40 HU were used to diagnose liver fat presence and >30% liver fat content, respectively. Logistic regression estimated cross-sectional associations of immune cell subsets with liver fat parameters adjusted for risk factors. We hypothesized higher proportions of non-classical monocytes, Th1, Th17, and memory CD4+ T cells, and lower proportions of classical monocytes and naive CD4+ T cells, were associated with liver fat. Exploratory analyses evaluated additional immune cell phenotypes (n=19). Results: None of the hypothesized cells were associated with presence of liver fat. Higher memory CD4+ T cells were associated with >30% liver fat content, but this was not significant after correction for multiple hypothesis testing (odds ratio (OR): 1.31, 95% confidence interval (CI): 1.03, 1.66). In exploratory analyses unadjusted for multiple testing, higher proportions of CD8+CD57+ T cells were associated with liver fat presence (OR: 1.21, 95% CI: 1.02, 1.44) and >30% liver fat content (OR: 1.34, 95% CI: 1.07, 1.69). Conclusions: Higher circulating memory CD4+ T cells may reflect liver fat severity. CD8+CD57+ cells were associated with liver fat presence and severity, but replication of findings is required.